Complexities and challenges of translating intervention success to real world gait in people with Parkinson’s disease - Lang, Charlotte; van Dieen, Jaap H.; Brodie, Matthew A.; Welzel, Julius; Maetzler, Walter; Singh, Navrag B.; Ravi, Deepak K. (Frontiers in Neurology, 2024)
Background Unstable gait leading to falls negatively impacts the quality of life in many people with Parkinson’s disease (PD). Systematic review evidence provides moderate to strong evidence of efficacy for a wide range of physiotherapy-based interventions to reduce gait impairment. However, outcomes have often focused on gait assessments conducted in controlled laboratory or clinical environments. Objective This perspective investigates the complexities and challenges of conducting real-world gait assessments in people with PD and the factors that may influence the translation from improved lab-assessed gait to improved real-world gait. Methods Through a thorough review of current literature, we present an in-depth analysis of current methodological approaches to real-world gait assessments and the challenges that may influence the translation of an intervention’s success from lab-based outcomes to improved walking during daily life. Results We identified six key factors that may influence the translation of intervention success into real-world environments at different stages of the process. These factors comprise the gait intervention, parameters analyzed, sensor setup, assessment protocols, characteristics of walking bouts, and medication status. We provide recommendations for each factor based on our synthesis of current literature. Conclusion This perspective emphasizes the importance of measuring intervention success outside of the laboratory environment using real-world gait assessments. Our findings support the need for future studies to bridge the gap between proven efficacy for gait as assessed in controlled laboratory environments and real-world impact for people with PD.